Dampak Pembelajaran Online di Tengah Pandemi Covid-19 Terhadap Proses Pembelajaran Metode Yanbu’a di Kelas 2 MI At-Taqwa Bondowoso - Tsuroya, Fatia Inast (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2020)
The purpose of this study was to identify and obtain information about the impact of the Covid-19 pandemic on the learning process of the Koran using the Yanbu'a DI method in grade 2 at MI At-Taqwa Bondowoso. The research used an exploratory case study method and the research approach used a qualitative case study method which was used to obtain information on the constraints and consequences of the COVID-19 pandemic on teaching and learning activities at MI At-Taqwa Bondowoso. Sample size is based on attainment of depth and richness of description. According to Guetterman, sample size is not a matter of representative opinion and views, but rather a matter of information wealth. The results of this study were that the researchers found several problems and obstacles experienced by students and class teachers in online teaching and learning activities, including: students were not active in depositing their reading results due to network constraints, no quota, students did not have communication tool or handpohne itself, the enthusiasm of students in learning begins to decline, therefore the goals and targets to be achieved by MI At-Taqwa Bondowoso are like their original ideals, that students are able to read the Koran properly and correctly, including in the form of letters, characteristics Characteristics of letters and proper fashohah experience many obstacles as a result of online learning.